Face mist Formulation from Fragrant Pandan Leaf Extract (Pandanus amaryllifolius Roxb.) As a Facial Moisturizer - Amilia Rusda; Mida Pratiwi; Riza Dwiningrum; Wina Safutri (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Healthy facial skin requires proper care to maintain moisture and prevent damage caused by free radicals. With the increasing public interest in natural-based cosmetics, fragrant pandan leaves (Pandanus amaryllifolius Roxb.) have become a potential candidate because they contain flavonoids, alkaloids, saponins, tannins, and polyphenols that possess antioxidant properties. This study used an experimental research design aimed at formulating a face mist preparation based on pandan leaf extract and determining the optimal concentration as a facial moisturizer. The extract was obtained using the maceration method with 96% ethanol and then formulated into four concentrations: 0% (blank), 5% (F1), 10% (F2), and 15% (F3). The evaluations included organoleptic test, pH, homogeneity, spray spreadability, drying time, specific gravity, stability, and moisture level. The evaluation results of the preparations showed good outcomes for organoleptic properties, homogeneity, pH, spray spreadability, specific gravity, and drying time. The stability test of the formulations F0, F1, F2, and F3 indicated stable results. The moisture test showed an increase in skin moisture with the average values after application of F0 (Blank) 58.6%, F1 (5%) 59.2%, F2 (10%) 59.4%, and F3 (15%) 57%. The study concludes that the face mist preparation containing fragrant pandan leaf extract (Pandanus amaryllifolius Roxb.) at all tested concentrations is capable of providing a good moisturizing effect on the skin.